2023
DOI: 10.3389/fphar.2023.1103265
|View full text |Cite
|
Sign up to set email alerts
|

Echinocystic acid alleviated hypoxic-ischemic brain damage in neonatal mice by activating the PI3K/Akt/Nrf2 signaling pathway

Abstract: Neonatal hypoxic-ischemic encephalopathy (HIE) is considered a major cause of death and long-term neurological injury in newborns. Studies have demonstrated that oxidative stress and apoptosis play a major role in the progression of neonatal HIE. Echinocystic acid (EA), a natural plant extract, shows great antioxidant and antiapoptotic activities in various diseases. However, it has not yet been reported whether EA exerts a neuroprotective effect against neonatal HIE. Therefore, this study was undertaken to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In addition, the Nrf2/HO-1 pathway is also a crucial pathway for antioxidant defense (Su et al, 2020 ). Following oxidative stress, Nrf2 separates from Keap-1, combines with the antioxidant response element (ARE), and then elevates the expression of some antioxidant-encoding proteins, which protect against oxidative stress in ALI (Li Y. et al, 2023 ). Bi et al have revealed that activating the Nrf2/HO-1 pathway can reduce oxidative stress in ALI mice.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Nrf2/HO-1 pathway is also a crucial pathway for antioxidant defense (Su et al, 2020 ). Following oxidative stress, Nrf2 separates from Keap-1, combines with the antioxidant response element (ARE), and then elevates the expression of some antioxidant-encoding proteins, which protect against oxidative stress in ALI (Li Y. et al, 2023 ). Bi et al have revealed that activating the Nrf2/HO-1 pathway can reduce oxidative stress in ALI mice.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that phosphorylation of Akt had the ability to reduce cellular apoptosis and ease neuroinflammation in diverse pathophysiological conditions [ 47 49 ]. On the other hand, Akt signaling has been reported to regulate the Nrf2 transcription factors, which aid in suppressing oxidative stress and negatively modulating the inflammatory response [ 27 29 , 50 ]. Numerous studies have indicated that Nrf2 contributed to modulating the functional phenotype of microglia and enhancing microglial phagocytosis in brain injury [ 26 , 51 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the PI3K/Akt signaling also promotes the detachment of Nrf2 from KEAP1, facilitates its translocation to the nucleus, and regulates Nrf2 activation in a ROS-dependent manner [ 106 , 107 ]. The induction of the PI3K/Akt/Nrf2 signaling axis ameliorates oxidative stress and apoptosis via the regulation of Nrf2, NQO1, and HO-1 [ 108 ].…”
Section: Nqo1: the Regulatory Pathwaysmentioning
confidence: 99%